Optical spectroscopy of the recurrent nova RS Ophiuchi – from the outburst of 2006 to quiescence. Issue 3 (20th December 2017) - Mondal, Anindita; Anupama, G C; Kamath, U S; Das, Ramkrishna; Selvakumar, G; Mondal, Soumen
Abstract: Optical spectra of the 2006 outburst of RS Ophiuchi beginning one day after discovery to over a year after the outburst are presented here. The spectral evolution is found to be similar to that in previous outbursts. The early-phase spectra are dominated by hydrogen and helium (i and ii ) lines. Coronal and nebular lines appear in the later phases. Emission line widths are found to narrow with time, which is interpreted as a shock expanding into the red giant wind. Using the photoionization code cloudy, spectra at nine epochs spanning 14 months after the outburst peak, thus covering a broad range of ionization and excitation levels in the ejecta, are modelled. The best-fitting model parameters indicate the presence of a hot white dwarf source with a roughly constant luminosity of 1.26 × 10 37 erg s −1 . During the first three months, the abundances (by number) of He, N, O, Ne, Ar, Fe, Ca, S and Ni are found to be above solar abundances; the abundances of these elements decreased in the later phase. Also presented are spectra obtained during quiescence. A photoionization model of the quiescent spectrum indicates the presence of a low-luminosity accretion disc. The helium abundance is found to be subsolar at quiescence.